Association of autoantibody specificity and response to intravenous immunoglobulin G therapy in immune thrombocytopenia: a multicenter cohort study. (April 2014) - Peng, J.; Ma, S.‐H.; Liu, J.; Hou, Y.; Liu, X.‐M.; Niu, T.; Xu, R.‐R.; Guo, C.‐S.; Wang, X.‐M.; Cheng, Y.‐F.; Ni, H.; Hou, M.
Summary Background Immune thrombocytopenia (ITP) is a common autoimmune bleeding disorder, in which platelet glycoprotein (GP)IIb–IIIa and GPIb–IX are the two most frequently targeted autoantigens. Our previous studies in animal models of ITP demonstrated that intravenous immunoglobulin G (IVIG) could protect against anti‐GPIIb–IIIa autoantibody‐mediated thrombocytopenia but failed to ameliorate ITP induced by most anti‐GPIb–IX autoantibodies. Objectives The objective of this human study was to evaluate the association between the specificity of antiplatelet autoantibodies and response to IVIG treatment. Patients/Methods In this retrospective study, a cohort of 156 previously untreated adults with severe ITP who underwent IVIG therapy (0.4 g kg−1 day−1 for 5 days) was analyzed. The primary outcome was response defined as platelet counts of ≥ 30 × 109 L−1 and a doubling of baseline counts within 7 days of dosing, and an absence of bleeding. Results and Conclusions Among the 66 patients with anti‐GPIb–IX autoantibodies, only 24 (36.4%) achieved a response, as compared with 72 of 90 patients (80.0%) who were negative for anti‐GPIb–IX autoantibodies (relative risk 2.2; 95% confidence interval 1.6–3.1). This study found no difference in response between patients with anti‐GPIIb–IIIa autoantibodies (61.7%) and those without anti‐GPIIb–IIIa autoantibodies (61.3%). Logistic regressions, including main effects and the interaction between these two autoantibodies, showed no influence of anti‐GPIIb–IIIa autoantibodies on the effects of anti‐GPIb–IX autoantibodies with regard to their association with IVIG response. Thus, in adults with ITP, the presence of anti‐GPIb–IX autoantibodies is a predictive factor for poor response to IVIG treatment. Trial registration: ClinicalTrials.gov NCT01666795.